Role of MicroRNAs and their corresponding ACE2/Apelin signaling pathways in hypertension. (January 2022) - Ali, Farman; Shen, Aling; Islam, Waqar; Saleem, Muhammad Zubair; Muthu, Ragunath; Xie, Qiurong; Wu, Meizhu; Cheng, Ying; Chu, Jiangfeng; lin, Wei; Peng, Jun
Abstract: Hypertension is controlled via the alteration of microRNAs (miRNAs), their therapeutic targets angiotensin II type I receptor (AT1R) and cross talk of signaling pathways. The stimulation of the Ang II/AT1R pathway by deregulation of miRNAs, has also been linked to cardiac remodeling as well as the pathophysiology of high blood pressure. As miRNAs have been associated to ACE2/Apelin and Mitogen-activated protein kinases (MAPK) signaling, it has revealed an utmost protective impact over hypertension and cardiovascular system. The ACE2-coupled intermodulation between RAAS, Apelin system, MAPK signaling pathways, and miRNAs reveal the practicalities of high blood pressure. The research of miRNAs may ultimately lead to the expansion of an innovative treatment strategy for hypertension, which indicates the need to explore them further at the molecular level. Therefore, here we have focused on the mechanistic importance of miRNAs in hypertension, ACE2/Apelin signaling as well as their biological functions, with a focus on interplay and crosstalk between ACE2/Apelin signaling, miRNAs, and hypertension, and the progress in miRNA-based diagnostic techniques with the goal of facilitating the development of new hypertension-controlling therapeutics. Highlights: Hypertension is modulated via the alteration of microRNAs (miRNAs). miRNAs have been associated to ACE2/Apelin signaling. MAPK signaling pathways reveal the practicalities of high blood pressure. Here we have focused on the mechanistic importance of miRNAs in hypertension. We also discussed ACE2/Apelin signaling and crosstalk between miRNAs.